Association of Obesity with Increased Rate of Postoperative Superficial Sternal Wound Infection after Coronary Artery Bypass Grafting Surgery - Amna Abbas, Aftab Yunus, Hina Aftab, Muhammad Athif Akram, Yahya Saeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to find association of obesity with postoperative superficial sternal wound infection after CABG. Study Design: This was a prospective comparative study. Place and Duration: This study was conducted at the Cardiac surgery Department, PIC, Jail Road, Lahore from 1st July 2020 to 31st Dec 2020. Methodology: Non probability / purposive sampling technique was used. A total of 140 patients (70 in each group) following inclusion criteria were enrolled in this study. Quantitative and qualitative variables were filled to the predesigned performa. A detailed social and demographic profile (age, gender, height, weight, BMI). Clinical history, i.e. (Diabetes Mellitus, Smoking, Hypertension) and clinical trials were assessed, i.e. preoperative EF (percent) was calculated. Using SPSS Version 24.0.0, statistical analysis was carried out. Qualitative variables such as gender, risk factors such as DM, HTN, smoking, and superficial sternal infection were represented as percentages, whereas quantitative variables such as age, height and weight were described as mean ± standard deviation. Chi-square test was used to determine the association of obesity with infection of sternal wound. P value≤0.05 was considered as significant. Results: The mean age of cases in this study in obese and non-obese group was 47.80 ± 9.79 years and 51.23 ± 9.36 years. There were 70(50%) obese patients and 70(50%) non-obese patients in our study. There were 59(84.29%) cases in obese group and 15 (21.43%) case in non-obese group who had developed post-operative infection, p-value was <0.001 which was highly significant showing strong association between postoperative infection and obesity. Conclusion: Sternal wound infection was a significant outcome in our research. We found strong association of obesity with post-operative sternal wound infection. Keywords: CABG, Diabetes, Obesity, Post-operative infection